Konstruksi Sosial dan Politik dalam Perkembangan Pendidikan Islam - Aini, Nur Lathifah; Najuasah Putra; Muhtadi Abdul Mun’im (Indo-MathEdu Intellectuals Journal, 2023)
Social and political life has a significant influence on the development of Islamic education, thus requiring in-depth study to find its development construction in the national education map. For this reason, this article will focus its study on how social and political systems affect the development of Islamic education by examining the construction of social and political systems. This research uses a qualitative approach to library research to explore, examine, and identify study topics in the literature. Both primary and secondary data sources are analyzed using text analysis techniques by reading literature data, identifying, and classifying data according to discussion, then discussing and presenting to obtain conclusions based on the focus of the study. The results oh the study show among others1) the political map of education policy in Indonesia provides direction for the development of Islamic education with the development of curriculum substance; 2) social and political systems have a reciprocal impact on the development of Islamic education. On the one hand, the social and political system has a significant impact on education, on the other hand, education shapes the social and political system; 3) the reorientation of Islamic education can balance the lag by answering the challenges of the times, covering the weaknesses of Islamic education, and returning Islamic education to its functional basis